SANAL DÜNYANIN SERGİLERİ - Tekin, Elvan (İnönü Üniversitesi, 2022)
Son yıllarda ülkemizde ve tüm dünyada yoğun şekilde etkisini gösteren Covid-19 pandemisi, hayatın hemen hemen her alanını ciddi şekilde sekteye uğratmış ve bu durumdan en çok eğitim-öğretim faaliyetleri zarar görmüştür. Eğitim-öğretimin ilköğretimden üniversiteye kadar olan tüm kademelerinde çevrim-içi ders faaliyetleri yürütülmüş ancak, günümüzde pandeminin seyri dolayısıyla, bu durum hibrit eğitim modeliyle yüz yüze ve çevrim-içi eğitim olarak devam etmektedir. Bununla birlikte, yaşamın her alanında görülen kapanma akademik hayatı ve sanat platformlarını derinden etkilemiştir. İzleyiciye, sanat alıcısına ulaşabilmek adına pek çok yeni kavramı kültür-sanat dünyasına dâhil edilmiştir. Çevrim-içi konserler, çevrim-içi tiyatro etkinlikleri, çevrim-içi paneller, çevrim-içi sergiler olarak kendisine yeni bir yol açma gereği duymuştur. Pandemi şartlarına göre yeniden şekillenen sergileme tasarımı kavramı yeni bir sunuş biçimini sanat alanına dâhil etmiştir. Ulaşılabilir olması ve fiziksel olarak salt bir mekâna bağlı olmaması “çevrim-içi sergileme tasarımı” kavramında anlam kazanmıştır. Araştırmanın ana ekseni çevrim-içi sergileme tasarımlarının sayısal bir ortamda ziyaretçilere sunuluş biçimini ve bu sunumun gerçekliği yakalama adına nasıl bir platform üzerine yapılandırıldığı konusunu içermektedir. Araştırmada bu yeni sergileme tasarımının uygulanabilirlik ve erişebilirlik açısından incelemesi yapılmış ve örnekler üzerinden değerlendirilmiştir. Yeni bir sergileme tasarımı anlayışının etraflıca incelenmiş olması alana meraklı araştırmacılara yol gösterici olması bakımından önemlidir.

The Covid-19 pandemic, which has had a profound impact in our country and all over the world in recent years, has seriously disrupted almost every field of life and education-training activities have suffered the most from this disruption. Online course activities have been carried out at all levels of education from primary schools to university, however, due to the course of the pandemic today, this activity is continued as face-to-face and online education through the hybrid education model. On the other hand, the shutdowns experienced in all field of life has deeply affected academic life and art platforms. In order to reach out the audience and the art buyer, many new concepts have been introduced to the world of culture and art. The world of culture and art has felt the need to open a new path for itself in the form of online concerts, online theater events, online panels and online exhibitions. Being reshaped on the basis of the pandemic conditions, the concept of exhibition design has included a new presentation form in the field of art. The fact that it is accessible and physically free from a mere space has gained meaning in the concept of "online exhibition design". As mentioned in the conclusion part of the research; The online display design, which will become a part of life after the pandemic, has taken on a more realistic structure with the importance of the metaverse concept. It has provided an important experience in terms of the fact that the virtual environment can be touched physically and its own self and experiences can be felt on a personal basis. Visitors were able to freely navigate from anywhere in the world, and were able to convey their experiences, likes or dislikes through social media connections. The main axis of the research includes the way online exhibition designs are presented to visitors in a digital environment and the platform on which this act of presentation is structured to capture reality. In the study, this new exhibition design is examined in terms of viability and accessibility and evaluated through samples. It is important in terms of guiding researchers, who are interested in the field, since a new understanding of exhibition design is thoroughly examined.
EXHIBITIONS OF THE VIRTUAL WORLD